Answer:
1. d) = g)
(3x - 2)(9x² + 6x + 4) = 27x³ - 8
2. e) = f)
(3x + 5) (3x - 4) = 9x² + 3x - 20
3. b) = h)
9x² - 24xy + 16y² = (3x - 4y)²
Explanation:
From the above question, we are to find the pairs through expansion or factorisation
a) (3x + 2)(9x² - 6x + 4)
b) 9x² - 24xy + 16y²
c) (4x - 3y)²
d) (3x - 2)(9x² + 6x + 4)
e) (3x + 5) (3x - 4)
f) 9x² + 3x - 20
g) 27x³ - 8
h) (3x - 4y)²
a) (3x + 2)(9x² - 6x + 4)
We expand.
3x(9x² - 6x + 4) + 2(9x² - 6x + 4)
27x³ - 18x² + 12x + 18x² - 12x + 8
27x³ - 18x² + 18x² + 12x - 12x + 8
= 27x³ + 8
c) (4x - 3y)²
We expand
(4x - 3y) (4x - 3y)
4x(4x - 3y) - 3y ( 4x - 3y)
16x² - 12xy - 12xy + 9y²
16x² - 24xy + 9y²
d) (3x - 2)(9x² + 6x + 4)
We expand
3x(9x² + 6x + 4) - 2(9x² + 6x + 4)
27x³ + 18x² + 12x - 18x² - 12x - 8
27x³ - 18x² + 18x² + 12x - 12x - 8
= 27x³- 8
e) (3x + 5) (3x - 4)
We expand
3x(3x- 4) +5(3x - 4)
9x² - 12x + 15x - 20
9x² +3x - 20
h) (3x - 4y)²
We expand
(3x - 4y) ( 3x - 4y)
3x(3x - 4y) -4y(3x - 4y)
9x² - 12xy - 12xy - 16y²
9x² - 24xy - 16y²
Hence:
1. d) = g)
(3x - 2)(9x² + 6x + 4) = 27x³ - 8
2. e) = f)
(3x + 5) (3x - 4) = 9x² + 3x - 20
3) b) = h)
9x² - 24xy + 16y² = (3x - 4y)²